ANALISIS PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pelanggan Kafe Terserah Kopi Malang) - Mila Amalia; Agus Widarko; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2020)
Abstract The rise of the cafe business in Malang city and huge potential market, requires businessman to create creativity for making their business look different so that it attracts consumer interest. The cafe owner have to know what the customer's needs and provide the satisfaction that expected by consumers so that consumers become loyal. This study aims to determine the effect of service quality and price on customer loyalty with satisfaction as an intervening variable in customers of Cafe Terserah Kopi Malang. This type of research in this research is explanatory research through quantitative approach. The population in this reasearch were customers of Cafe Terserah Kopi Malang with total of sample is 96 respondents who were selected using a purposive sampling technique. In this research, using questionnaires and interviews for data collection methods. The data analysis method use path analysis. The results showed that service quality has a direct effect on satisfaction, price has a direct effect on satisfaction, service quality has a direct effect on customer loyalty, price has a direct effect on customer loyalty, satisfaction has a direct effect on customer loyalty, and service quality and price has an indirect effect on customer loyalty with satisfaction as an intervening variable. Keyword: Service Quality, Price, Satisfaction, Customer Loyalty.